Comparative study of ethno-social processes and ethnonational policy in the regions of Siberia - Yuri V. Popkov; Olga A. Persidskaia (Novye Issledovaniâ Tuvy, 2016)
Article presents the first results of a comparative study of ethno-social processes in the three regions of the Russian Federation: Novosibirsk region, Khanty-Mansi Autonomous district and the Republic of Altai. The specificity of the regions expressed through particularity of ethno-social situation, the nature of interethnic relations, the attitudes of the inhabitants of regions to migrants, the level and causes of ethnic tension.